Cold war - a new oral history of life between east and west - Kendall, Bridget (London BBc Books, 2017)
From pilots making food drops during the Berlin Blockade and Japanese fishermen affected by H-bomb testing to families fleeing the Korean War and children whose parents were victims of McCarthy's Red
1
Keywords: Cold war